쓰기 처리 과정에서 전두엽의 기능 - 김영만(Young Man Kim); 이은섭(Eunseop Lee); 신준수(Joon Soo Shin); 김효정(Hyo Jeong Kim); 안서경(Seo Kyung An); 윤지혜(Ji Hye Yoon) (언어치료연구, 2024)
목적: 전두엽은 인간의 뇌에서 언어, 인지 및 운동 기능을 포함한 고등 인지 처리에 중요한 역할을 담당한다. 쓰기는 집행기능, 작업기억, 주의력 등과 더불어 언어 능력, 운동 계획 및 프로그래밍까지의 고차원적인 활동을 요구한다. 본 연구에서는 쓰기의 중추와 말초 처리 과정에서 전두엽의 역할을 살펴보고 실서증 양상과 관련지어 분석해보고자 한다. 방법: 문헌 검색을 위해 ‘Pubmed’ 검색엔진을 활용하였으며, 1948년 1월 1일부터 2024년 4월 1일까지 ‘handwriting’, ‘agraphia’, ‘frontal’ 등의 키워드를 조합하여 검색하였다. 총 658편의 논문이 검색되었으며, 최종적으로 18편의 논문이 선택되었다. 결과: 총 18편의 문헌을 실서증 양상에 따라 분류하였으며, 중추적 단계에 해당하는 문헌 8편, 말초적 단계에 해당하는 문헌 9편, 중추 및 말초를 모두 포함하는 문헌 1편이었다. 중추적 단계에 해당하는 어휘실서증 1편, 음운실서증 5편, 어휘와 음운실서증을 모두 보고한 연구 1편, 그리고 심층실서증 2편이었다. 말초적 단계에 해당하는 이서 장애 3편, 실행실서증 5편, 공간실서증은 1편이었다. 결론: 전두엽의 손상은 어휘 및 음운 철자 처리와 운동 계획을 포함한 중추 및 말초적 단계 모두에 영향을 미치며 세부적인 병소에 따라 상이한 양상의 쓰기 장애로 나타났다. 쓰기의 중추 처리 과정에서 전두엽은 저장된 철자 정보를 표현하기 위한 어휘 선택 및 탐색, 그리고 음운 정보의 변환에 관여하며, 말초 처리 과정에서 철자에 대한 정보를 구체적인 글자의 형태로 산출하는 운동 계획으로 변환하는 기능을 담당한다. 본 연구 결과는 전두엽 손상으로 나타나는 쓰기 오류에 대한 양상 확인과 실서증에 대한 감별 진단 시 참고할 수 있는 기초 자료가 될 수 있다. Purpose: The frontal lobe plays a crucial role in higher cognitive processing, encompassing language, cognitive, and motor functions. Writing requires complex cognitive processing such as executive function, working memory, and attention, as well as language, motor planning, and programming. This review investigates the roles of the frontal lobe in central and peripheral processes of writing. Methods: The ‘Pubmed’ search engine was used to conduct a literature search using a combination of keywords such as ‘handwriting’, ‘agraphia’, and ‘frontal’ from 1948 to April 1, 2024. A total of 658 papers were searched and 18 were selected. Results: A total of 18 research papers were classified according to the pattern of agraphia, with 8 corresponding to the central, 9 corresponding to the peripheral process, and 1 corresponding to both. The research of central agraphia included 1 case of lexical, 5 phonological, 1 including both lexical and phonological agraphia, and 2 deep agraphia. There were 3 research papers on allographic, 5 apraxic, and 1 spatial agraphia, which correspond to the peripheral process. Conclusions: Damage to the frontal lobe affects both the central and peripheral stages of writing processes, including lexical and phonological processing as well as motor planning, resulting in various types of writing disorders depending on the specific lesion. In the central process, the frontal lobe involved in lexical selection and retrieval for producing stored graphemic representation and in the conversion of phonological information. In the peripheral process, it is responsible for converting graphemic representation into motor plans that produce specific forms of letters. This study provides fundamental data that can be referenced for identifying patterns of writing errors caused by frontal lobe damage and for differential diagnosis of agraphia. KCI Citation Count: 0